2017
DOI: 10.1021/acsbiomaterials.7b00827
|View full text |Cite
|
Sign up to set email alerts
|

Design Redox-Sensitive Drug-Loaded Nanofibers for Bone Reconstruction

Abstract: Implantation of a scaffold into the body in a safe and convenient manner remains a challenge in the repair of patient bone defect. In the present study, a strategy for fabrication of the redox-sensitive nanofibers with a core−shell structure that can deliver the growth factors in a tunable manner is presented. Poly(ethylene oxide) (PEO) and bone morphogenetic protein 2 (BMP-2) forms the inner core region, and a mixture of poly(epsilon-caprolactone) (PCL) and redox-responsive c-6A PEG−PCL nanogel with −S−S− bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Gong et al engineered novel, redox‐responsive, core–shell structured fibers for controlled release of BMP‐2 for mandibular bone defect regeneration ( Figure ). [ 111 ] BMP‐2 was encapsulated in the core region with Poly(ethylene oxide) (PEO), and the outer shell was composed of poly(ε‐caprolactone) (PCL) and redox‐responsive nanogels (crosslinked 6‐arm PEG‐polycaprolactone/6‐arm PEG‐polycaprolactone‐sulfhydryl nanogels, c‐6A PEG‐PCL/6A PEG‐PCL‐SH NGs). The degradation of nanogels was controlled by GSH levels resulting in the formation of nanochannels inside the nanogel and increasing shell permeability and drug release from the inner region.…”
Section: Stimuli‐responsive Growth Factor Delivery Systems In Tissue mentioning
confidence: 99%
See 1 more Smart Citation
“…Gong et al engineered novel, redox‐responsive, core–shell structured fibers for controlled release of BMP‐2 for mandibular bone defect regeneration ( Figure ). [ 111 ] BMP‐2 was encapsulated in the core region with Poly(ethylene oxide) (PEO), and the outer shell was composed of poly(ε‐caprolactone) (PCL) and redox‐responsive nanogels (crosslinked 6‐arm PEG‐polycaprolactone/6‐arm PEG‐polycaprolactone‐sulfhydryl nanogels, c‐6A PEG‐PCL/6A PEG‐PCL‐SH NGs). The degradation of nanogels was controlled by GSH levels resulting in the formation of nanochannels inside the nanogel and increasing shell permeability and drug release from the inner region.…”
Section: Stimuli‐responsive Growth Factor Delivery Systems In Tissue mentioning
confidence: 99%
“…ROS responsive nanofiber for BMP‐2 delivery with core–shell structure designed for bone regeneration. [ 111 ] A) Schematic of the fabrication of the nanogel‐in‐nanofiber device and the ROS responsive delivery via ROS‐induced degradation of the nanogel and the nanochannels formed to promote the diffusion rate of BMP‐2 loaded in the core of nanofiber. B) TEM images of nanogel.…”
Section: Stimuli‐responsive Growth Factor Delivery Systems In Tissue mentioning
confidence: 99%
“…The processes after that are similar to a conventional electrospinning, in which a collector is used to carry fibers. Co-axial electrospinning permits various materials, including polymers [46,47], oligomers [48], inorganic compounds [37], proteins [47], and biomolecules [41], to be immobilized into the core component of the core-shell nanofibers. Due to the functions of the core component, the core-shell nanofiber has more beneficial properties for bone tissue engineering.…”
Section: Multi-axial Electrospinning (Core-shell Nanofiber)mentioning
confidence: 99%
“…Gong et al demonstrated drug delivery by nanofibers for bone regeneration. Poly(ethylene oxide) (PEO) containing bone morphogenetic protein 2 (BMP-2) was used as the inner core and poly-ε-caprolactone (PCL) was used as the outer shell [47]. Shalumon et al fabricated silk fibroin (SF)/chitosan (CS)/nanohydroxyapatite (nHAP) nanofibers embedded with BMP-2 in the core of the nanofiber [50].…”
Section: Multi-axial Electrospinning (Core-shell Nanofiber)mentioning
confidence: 99%
“…(B) Table-top SLA method to obtain porous hydrogel-based scaffolds that emulate the transitional nature of the osteochondral region by the inclusion of a gradient of nHA (adapted from Castro et al, 2015 , with permission from The Royal Society of Chemistry). (C) Redox-responsive nanofibers allow the controlled BMP-2 release for bone regeneration in rat model (reprinted with permission from Gong et al, 2018 , copyright American Chemical Society).…”
Section: Nanofibrous Scaffoldsmentioning
confidence: 99%